PERANAN HUKUM DALAM PENGEMBANGAN INDUSTRI PERTAHANAN SEBAGAI INDUSTRI STRATEGIS DIDALAM MENJAGA KEDAULATAN NEGARA KESATUAN REPUBLIK INDONESIA - Purnamasari Faujura, Rahamanisa (Universitas Wiralodra, 2019)
Indonesia's geographical located between two continents and oceans, those are the Asian nd the Australian Continent, and the Indian and the Pacific Ocean, has made Indonesia to become a country with strategic position, both for the world trade route and inter-State relations. But on the other hand Indonesia has the sovereignty of the State that must be guarded and maintained from all kinds of threats both from within and outside. For this reason, Indonesia is required to have the capacity in the form of TNI defense equipment, which is adequate as the main instrument to protect territorial sovereignty and to safeguard national interests from the threats, challenges, obstacles and disturbances both from domestic and foreign. Therefore, the development of the defense industry is also needed. The main problem in this study is how does the law regulate the development of defense industry as Indonesia's strategic industry?The descriptive method of analysis with normative juridical was used in analyzing the problems of the development of the defense industry in facing the challenges, threats, and disruptions to the Republic of Indonesia's sovereignty as a consequence of the strategic location of Indonesia's geographical position. The results of the study show that the defense industry has a position as a strategic industry, because the primary weaponry defense system has important role in order to maintain the sovereignty of the State. Even though the regulation has been assigned in a law, namely Law Number 16 of 2012 concerning on the Defense Industry, but it has not been regulated by clear regulations and is tend to ad hoc, which is certainly not beneficial for the growth and development of the National defense industry. Law as a medium of renewing society must be able to make changes, so that it can direct where the national defense industry will be developed, so it is able to create companies that are reliable in producing defense equipment to preserve national sovereignty.